Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.heliyon.2019.e03045
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent nicotine exposure to prenatal alcohol consumption alters the hippocampal and cortical neurotoxicity

Abstract: This study investigated the neurotoxic effects of prenatal alcohol and nicotine exposure in the cortex and hippocampus of rodents. Main methods: Behavioral alterations, electrophysiological changes, and biochemical markers associated with cholinergic neurotransmission, neural oxidative stress, mitochondrial function, and apoptosis were evaluated. Key findings: Prenatal alcohol exposure induced the generation of ROS, nitrite and lipid peroxide, decreased mitochondrial Complex-I and IV activities, increased Casp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The AchE activities in all treatment groups increased significantly, which could have a consequential decrease in cognitive function [24]. Ach is among the central neurotransmitters, which play a significant role in memory, learning and cognition [25].…”
Section: Discussionmentioning
confidence: 98%
“…The AchE activities in all treatment groups increased significantly, which could have a consequential decrease in cognitive function [24]. Ach is among the central neurotransmitters, which play a significant role in memory, learning and cognition [25].…”
Section: Discussionmentioning
confidence: 98%
“…Another study also showed that alcohol toxification is lower in chronic smokers compared to non-smokers 87 . Recently, Bhattacharya et al 18 showed that prenatal ethanol exposure (10% v/v) could increase ROS production, LP, and caspases activities and also decrease spatial memory in F1 rats, while simultaneous exposure to ethanol and nicotine (6 mg/kg/day, by mini pump) could alleviate the adverse effects of ethanol on OS and hippocampal memory. However, they exposed pregnant rats to nicotine and ethanol at higher and lower doses, respectively, compared with the current study.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that consumption of any of these substances increase the desire for the other 17 . To date, some studies have investigated the effect of prenatal co-exposure to these substances on various tissue, but they have yielded conflicting results 18 ā€“ 21 . However, no study has evaluated the effect of developmental co-exposure to alcohol and nicotine on the testicular properties and sperm parameters of male offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Another study also showed that alcohol toxi cation is lower in chronic smokers compared to that of the non-smokers 60 . Recently, Bhattacharya and colleagues 61 showed that prenatal ethanol exposure (10% v/v) could increase ROS production, LP, caspases activities as well as decrease spatial memory in F1 rats, while simultaneous exposure to ethanol and nicotine (6 mg /kg/day, by mini pump) could alleviate the adverse effects of ethanol on oxidative stress and hippocampal memory. However, they exposed pregnant rats to nicotine and ethanol at higher and lower doses, respectively compared to our study.…”
Section: Discussionmentioning
confidence: 99%